2022
DOI: 10.1088/0256-307x/39/9/093201
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Nonsequential Double Ionization of Argon Atoms via Orthogonal Two-Color Field

Abstract: Using a three-dimensional classical ensemble model, we investigate the dependence of relative frequency and relative initial phase for nonsequential double ionization (NSDI) of atoms driven by orthogonal two-color (OTC) fields. Our findings reveal that the NSDI probability is clearly dependent on the relative initial phase of OTC fields at different relative frequencies. The inversion analysis results indicate that adjusting the relative frequency of OTC fields helps control returning probability and flight ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Li et al studied NSDI of Ar atoms using OTC laser fields with different wavelength combinations in the classical ensemble model, and found that changing the laser frequency in the OTC laser field can control the electron return probability and the direction of momentum of the doubly charged ions. [29] Gong et al used phase-controlled OTC laser pulses to study the time delay of photoelectron emission in strong-field ionization of Ar atoms. By controlling the relative phase, they were able to clearly distinguish the main peak and sideband peaks in the above-threshold ionization spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al studied NSDI of Ar atoms using OTC laser fields with different wavelength combinations in the classical ensemble model, and found that changing the laser frequency in the OTC laser field can control the electron return probability and the direction of momentum of the doubly charged ions. [29] Gong et al used phase-controlled OTC laser pulses to study the time delay of photoelectron emission in strong-field ionization of Ar atoms. By controlling the relative phase, they were able to clearly distinguish the main peak and sideband peaks in the above-threshold ionization spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] More intriguingly, experimental and theoretical studies have revealed that a strong dependence between the electron correlation characteristics and the relative initial phase of the OTC electric field. [26][27][28] In this paper, we conduct a theoretical investigation into the double ionization of neon atom in the OTC electric field using the semiclassical ensemble model. Our focus lies on the momentum distribution, which we examine by introducing a relative initial phase of 0.5π and varying the relative amplitude of the OTC electric field to explore the correlation characteristics of recolliding electrons in NSDI.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between laser and matter is highly nonlinear under certain physical conditions, and many new physical phenomena are produced. Such as high-order above-threshold ionization (HATI) [1], high harmonic generation (HHG) [2][3][4], nonsequential double ionization(NSDI) [5][6][7][8][9][10][11][12], etc. These phenomena can be understood with a three-step recollision mode [13].…”
Section: Introductionmentioning
confidence: 99%